The impact of social media in the sociolinguistic practices of the peripheral post-socialist contexts - Tankosic, Ana; Dovchin, Sender (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
This article examines the impact of social media on the linguistic and communicative practices in post-socialist countries, such as Bosnia and Herzegovina, Serbia, and Mongolia–the contexts very much under-represented in the discussion of translingualism. Relocalisation of social media-based linguistic resources in the languages used in these peripheral countries represents linguistically innovative practice, which entails orthographic, morphosyntactic, and phonologic adaptation of Facebook, Instagram, and YouTube labels, as well as their semantic reformulation in Bosnian, Serbian, and Mongolian resources. Social media-oriented linguistic terminologies are being adapted to the Cyrillic alphabet in Serbian and Mongolian and adopt grammatical features of the Bosnian variety. The original forms in social media are manipulated by social media users to serve their own ethos and local sociolinguistic practices. As a result, new forms of languages and linguistic meanings are created.